Alternative Metals for Homogeneous Catalyzed Hydroformylation Reactions. Issue 10 (21st February 2013) - Pospech, Jola; Fleischer, Ivana; Franke, Robert; Buchholz, Stefan; Beller, Matthias
Abstract Transition‐metal‐catalyzed hydroformylation reactions constitute one of the most powerful tools for CC bond formation in organic synthesis and represent an outstanding example of the application of homogeneous catalysis on an industrial scale. This process allows for the straightforward conversion of inexpensive chemical feedstock into broadly applicable aldehydes, which serve as major building blocks for numerous chemical products. These products are highly valuable for the chemical industry and used as plasticizers, detergents, and surfactants on a million ton scale. Moreover, aldehydes serve as versatile chemical intermediates for the production of fine chemicals and pharmaceuticals. Currently, most of the bulk hydroformylation processes rely on rhodium‐based catalysts. The increasing demand and resulting high cost of this precious metal has resulted in alternative transition‐metal catalysts becoming highly desirable. The following Review summarizes the progress achieved utilizing Ru, Ir, Pd, Pt, and Fe catalysts in hydroformylation reactions.